Manejo integrado del hongo Ceratocystis fimbriata causante de la enfermedad del marchitamiento vascular en Teca (Tectona grandis) - Escobar Arana., Karla Magaly (2021)
The cultivation of teak (Tectona grandis) in Ecuador and around the world is a source of great economic income, the commercialization of teak is very important for the cultivators of high value hardwood species. In Ecuador there are currently 50,000 planted hectares, this wood is one of the most valuable, of great value and prestige, although this crop is subject to pests and diseases throughout the year. Integrated disease management is the use of various control systems with the objective of controlling or eradicating the fungus that causes the disease that affects the crop. The fungus Ceratocystis fimbriata is the cause of the vascular wilt disease in teak. The presence of this disease has produced very large losses in plantations, deteriorating them and this in turn caused a decrease in their yield, creating concern and economic losses in producers since individuals have been found in very bad conditions, even dead trees standing. For this, there are several control methods: cultural, chemical and biological, which help to control the fungus, in order to obtain a better performance when cutting the trees. Key words: Ceratocystis fimbriata, integrated management, biological, fungus, vascular wilt